DAMPAK ASEAN – CHINA FREE TRADE AREA (AFTA) TERHADAP PERKEMBANGAN EKSPOR CRUDE PALM OIL (CPO) INDONESIA KE TIONGKOK - Lisa Pratama; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This reseacrh aim to explain about the eefect of the implementation of ASEAN - China Free Trade Area (ACFTA) on the development of Crude Palm Oil (CPO) export from Indonesia to Tiongkok. ACFTA is an agreemnet between the members of ASEAN and Tiongkok to make free trade. This research uses the qualitative descriptive as the method and secondary is the techniques of collection data. Futhermore author uses the librarism perspective with nation state as the level of analysis and uses the international trade with competitive advantage theories by David Ricardo. The result of this research shoe the export of Indonesian’s Crude Palm Oil (CPO) to Tiongkok having an increase since was implementated of ASEAN –China Free Trade Area in 2010, and the production of Indonesian’s Crude Palm Oil increased after the ASEAN – China Free Trade Agreement appliedKey Words: Export, Crude Palm Oil, ASEAN- China Free Trade Area, Bilateral relation, Free Trade Area.